Analysis Of Public Sentiment Towards The Free Nutritious Meal Program In Schools Based On Tweets Using The K-Nearest Neighbors Method - Maharani, Aiga Rizki; Gustriansyah, Rendra; irfani, muhammad haviz (Universitas Multi Data Palembang, 2025)
The public sentiment analysis of the free nutritious meal program in schools was conducted based on data from the social media platform Twitter (X). This program is an initiative by the Indonesian government aimed at improving the nutritional quality of children, particularly those from underprivileged families, as well as reducing stunting rates. The data used consisted of 3,007 tweets that had undergone preprocessing, manual labeling, and class balancing using oversampling techniques. The K-Nearest Neighbors (K-NN) method was applied to classify sentiment into three categories: positive, negative, and neutral. The data was split with 80% used for training and 20% for testing. The analysis process included data representation using TF-IDF and model evaluation using metrics such as accuracy, precision, recall, and F1-score. Evaluation results showed that the K-NN model with K=3 achieved an accuracy of 82%, with the best performance in classifying negative sentiment tweets (recall = 1.00, F1-score = 0.93). These findings indicate that public opinion toward the program tends to be negative, mainly due to concerns over budget allocation and food distribution. This study is expected to provide input for the government in designing more effective and responsive communication strategies and public policies.